The Role of Youtube in Optimizing The Cognitive Development of Early Children Group B on Theme Of Vehicles in RA Salafiyah Cibenda, Pangandaran District - Ai Teti Wahyuni; Aang Andi Kuswandi; Ai Niatus Saadah (International Journal of Education and Literature, 2023)
Early childhood is the age when a child is experiencing significant cognitive development. Providing the right stimulus in the form of role useYouTube is one effort to optimize children's cognitive development. The purpose of this research is to know and understand the roleYouTube in optimizing the cognitive development of Group B early childhood on the theme of vehicles at RA Salafiyah Cibenda Pangandaran Regency. The research method used is a qualitative-descriptive approach. The subjects in this study were students, teachers and parents from Group B at RA Salafiyah. Data collection techniques were carried out through observation, interviews and documentation. The results of the study show that the roleYouTube can optimize children's cognitive development. This can be seen from the developments that occur in the aspects of attention, concentration, imagination, curiosity, memory, and language, in early childhood regarding the role of usingYouTube group B on the theme of Vehicles in RA Salafiyah Cibenda Pangandaran Regency.